Jepang dan Isu Keamanan Energi: Dari Krisis Minyak Dunia hingga Politik Perubahan Iklim - Isnaeni, Nurul (Global: Jurnal Politik Internasional, 2006)
Among other industrialized countries, Japan represents a unique case for examination of the critical linkages of energy-environment-security. Since 1980 it has broadened the concept of its national security to include non-military issues, which stresses energy security at the point. The 1970s oil crisis altered the country’s approach to energy security so that dependence on imports would not adversely affect its economic growth. Since the mid 1980s, however, when global environmental issues turned into an international political agenda, Japan's quest for energy security seems to have met another challenge. This paper assumes that Japan’s institutional framework rely on the pragmatic roles of economies, politics and technology rather than ideology, providing a sound foundation for flexibility in producing policies that address the intricate problems of energy-environmental security.